ANALISIS PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP SOLVABILITAS PERUSAHAAN ASURANSI SYARIAH: STUDI PADA UNIT USAHA SYARIAH PT. BRI INSURANCE - Zahran Radja Hadaya Cholifi, (2022)
The profit of a company will be different from the previous period in each period. Profit fluctuations can be affected by a number of factors, including size and solvency. one of the factors that can affect the decline in profits is solvency, company size. This study aims to determine whether firm size, profitability affect solvency. The population in this study is the Sharia Business Unit of PT Asuransi BRI. and purposive sampling as the sampling method with the Criteria for the Financial Statements of the Sharia Business Unit of PT. BRI Insurance Period 2017-2021". The author reprocessed and obtained secondary data from financial statements for this study, which also used SPSS-assisted financial analysis and testing methods. The research results show that (1) company size has an effect on solvency, this is due to the high cost of insurance from large insurance companies, which increases the risk-based minimum capital level and affects the solvency ratio. (2) Profitability has no significant effect on solvency, it is believed that Indonesian sharia insurance companies do not make much profit, so solvency is more important to them than fulfilling obligations. (3) Simultaneously firm size and profitability have an effect on solvency. It shows that (1) Firm size has an effect on solvency, this is due to the high cost of insurance from large insurance companies, which increases the risk-based minimum capital level and affects the solvency ratio. (2) Profitability has no significant effect on solvency, it is believed that Indonesian sharia insurance companies do not make much profit, so solvency is more important to them than fulfilling obligations. (3) Simultaneously firm size and profitability influence solvency.